Environmental Criticism and the Value of Education: A Study on Indonesian Literary Cyber - Mutolib; Pamungkas, Onok Yayang (Canadian Journal of Language and Literature Studies, 2025)
This research is an effort to describe and explain the values of literary ecocriticism and education in poetry contained on the Riau Sastra website through a review of literary ecocriticism and educational values. The research method uses hermeneutics. Source: Research data is poetry from the Riau Sastra.com web. The results of the study show that the poems in Riau Sastra represent environmental pollution in the form of water, air and soil, excessive deforestation, exploitation of natural resources. And in it there are educational values. The poems in Riau Sastra represent natural exploitation, deforestation, water pollution, air pollution, natural disasters, and animal exploitation. In addition, the poems also represent educational values, which include religious, cultural, social and moral. Poems are not only as reading materials, but also as a source of messages, information that will have an impact on understanding the environment and educational value on the importance of protecting the environment. Therefore, it takes a strong effort to understand and provide an understanding of how important the value of criticism is in the environment and education using literary appreciation and one of them is poetry. In addition, efforts are needed to build an understanding of the importance of protecting the environment and aspects in it such as not polluting the environment, whether it is water, air and soil, not over-beating forests, exploitation of natural resources for future interests.